Strategi Pemasaran Syariah dan Peningkatan Penjualan: Studi Kasus Bakso Bang Karim Bangkalan - Achmad Junaidi; Syaiful Bahri; Amry Abdurrahman (AL-UJRAH, 2026)
Abstract This study aims to evaluate in depth the implementation of sharia marketing mix strategies at Bakso Bang Karim MSME in Karang Duwak Village, Bangkalan, and its impact on customer loyalty and sales volume. Using a descriptive qualitative approach with field research methods, primary and secondary data were collected through participatory observation techniques, sales record documentation studies, and in-depth interviews with business owners, employees, and loyal customers. Data analysis was conducted inductively through an interactive cycle comprising data reduction, descriptive narrative display, and conclusion drawing. The results show that Bakso Bang Karim has successfully and consistently integrated tawhid values and prophetic ethics (shiddiq, amanah, tabligh, fathanah) into the 4P marketing mix. The synergy between halalan thayyiban product quality assurance, fair pricing (‘adl), trustworthy distribution services, and honest promotion effectively mitigates gharar risk. Furthermore, the ethical adoption of digital technology strengthens customer engagement and triggers positive Word of Mouth (WOM) mechanisms. This holistic strategy has significant implications for increasing sustainable sales volume and achieving business blessings (falah). Keywords: Sharia Marketing Mix, Digital Marketing, Sales Volume, Customer Loyalty, Business Blessing